2006
DOI: 10.1142/s0219635206001057
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Assessment of Brain Function in Ptsd: Brain Stability and Working Memory

Abstract: Posttraumatic Stress Disorder (PTSD) is characterized by symptoms of hyperarousal, avoidance and intrusive trauma-related memories and deficits in everyday memory and attention. Separate studies in PTSD have found abnormalities in electroencephalogram EEG, in event-related potential (ERP) and behavioral measures of working memory and attention. The present study seeks to determine whether these abnormalities are related and the extent to which they share this relationship with clinical symptoms. EEG data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 58 publications
3
31
3
Order By: Relevance
“…It would follow from this argument that the inverse correlation between PTSD symptom severity and alpha power is a function of the relationship of both to TBI severity (in those whose TBI event meets the criteria for mTBI) and does not reflect a direct causal relationship between the decrease in alpha-band power and PTSD. However, the fact that reduced alpha power has been demonstrated in the setting of primary PTSD in previous studies (JokicBegic, 2003;Veltmeyer, 2006;Huang et al, 2014) and our finding of a correlation between the reduction in prefrontal alpha-band power and the specific PTSD symptom of emotional numbing argue against mTBI severity as the causative factor of two otherwise unrelated outcomes, i.e. the decrease in alpha-band oscillatory activity and the increase in susceptibility to PTSD.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…It would follow from this argument that the inverse correlation between PTSD symptom severity and alpha power is a function of the relationship of both to TBI severity (in those whose TBI event meets the criteria for mTBI) and does not reflect a direct causal relationship between the decrease in alpha-band power and PTSD. However, the fact that reduced alpha power has been demonstrated in the setting of primary PTSD in previous studies (JokicBegic, 2003;Veltmeyer, 2006;Huang et al, 2014) and our finding of a correlation between the reduction in prefrontal alpha-band power and the specific PTSD symptom of emotional numbing argue against mTBI severity as the causative factor of two otherwise unrelated outcomes, i.e. the decrease in alpha-band oscillatory activity and the increase in susceptibility to PTSD.…”
Section: Discussioncontrasting
confidence: 41%
“…Six of fifteen patients in Group 1 (40%) were taking medications that exert some pharmacological effect on the central nervous system as compared to nine of seventeen in Group 2 (53%). However, it has previously been demonstrated that there is no significant difference in alpha frequency between "medicated" and "non-medicated" patients with PTSD, although there are differences in power demonstrated at faster frequencies (Veltmeyer et al, 2006). Notably, approximately a third of Group 2 patients were taking Prazosin at the time of the recording.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The increased activation in the superior frontal cortex found in the present study might therefore be related to altered processing of negative emotions in PTSD, perhaps underlying the avoidance [43] , hypervigilance and emotional numbness [37] seen in PTSD. Consistent with this, a study of resting-state functional connectivity between the posterior cingulate and other brain regions in a group of acutely traumatized adults found that the degree of connectivity with bilateral anterior cingulate region is positively associated with the severity of PTSD symptoms (i.e., the most severe cases had the greatest coordinated activity between posterior and anterior cingulate) [7] .…”
Section: Discussionmentioning
confidence: 60%
“…It is possible that mixed-trauma samples prevent significant results from being achieved in the EEG studies. In fact, most of the studies that used a mixedtrauma sample found no significant correlation between EEG parameters and the severity of symptoms-very few exceptions were found (Lobo et al, 2014;Veltmeyer et al, 2009Veltmeyer et al, , 2006.…”
Section: Discussionmentioning
confidence: 95%